Rapid evidence profile #66: Exploring female-dominant conditions among military personnel and Veterans in each of the ‘Five Eyes’ countries - Waddell, K; Jaspal, A; Shivji, A; Ali, A; Bhuiya, AR; Wilson, MG (My University, 2024)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about female-dominant conditions among military personnel and Veterans in each of the ‘Five Eyes’ countries in response to a decision-maker’s request.
Keywords: female-dominant; military; Veterans; Five Eyes